Lysosomal processing of progranulin - Zhou, Xiaolai (Mol Neurodegener, 2017)
BACKGROUND: Mutations resulting in progranulin (PGRN) haploinsufficiency cause frontotemporal lobar degeneration with TDP-43-positive inclusions (FTLD-TDP), a devastating neurodegenerative disease. PGRN is localized to the lysosome and important for proper lysosome function. However, the metabolism of PGRN in the lysosome is still unclear. RESULTS: Here, we report that PGRN is processed into ~10 kDa peptides intracellularly in multiple cell types and tissues and this processing is dependent on lysosomal activities. PGRN endocytosed from the extracellular space is also processed in a similar manner. We further demonstrated that multiple cathepsins are involved in PGRN processing and cathepsin L cleaves PGRN in vitro. CONCLUSIONS: Our data support that PGRN is processed in the lysosome through the actions of cathepsins.